Pengembangan Prototype Startup Healthy Food “YumHealth” dengan Pendekatan Design thinking dan Usability Testing - Heni Widi Astuti; Vanishi Tiyar Nitza; Lasmi Sapalakai; Patrick Ezra Tua; Aldian Umbu Tamu Ama (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on the results of a survey by Kurious and Populix, a healthy lifestyle starting to become a focus and trend in Indonesia. These surveys reveal people's understanding of healthy food, with the problems that arise. Even though many people understand its benefits, there is still a gap between understanding and healthy practices, especially among the productive age group (25-44 years). Difficulty maintaining consistency in a healthy eating pattern is a challenge faced. The solutions provided from the survey results show that 64 percent of Indonesian people use healthy catering services to maintain consistent healthy lifestyle patterns. Therefore, the idea of developing the YumHealth startup emerged to help people start eating better, with a focus on catering services and delivery service features, nutritional consultations, education through articles,and a BMI calculator. This research will focus on implementing these features using a Design Thinking approach and testing using the Usability Testing method. Apart from that, the potential of the online market in Indonesia is also an encouragement to develop this application. This research aims to provide adequate solutions to existing problems and improve user experience. Based on the results of Usability Testing with 30 respondents, the final result was 71.5, which means the application prototype is in a good grade. The testing results also provide suggestions such as the use of typography (fonts), and visualization in education, as well as adding features such as guide pages and TDEE calculators.